Respostas
respondido por:
0
a 1 = ?
r = -5
a 51 = 243
a 51 = a 1 + (n - 1 ).-5
a 51 = a 1 + (51 - 1 ).-5
a 51 = a 1 + (50).-5
a 51 = a 1 + (-250)
a 51 = a 1 - 250
a 1 - 250 = a 51
a 1 - 250 = 243
a 1 = 243 + 250
a 1 = 493
r = -5
a 51 = 243
a 51 = a 1 + (n - 1 ).-5
a 51 = a 1 + (51 - 1 ).-5
a 51 = a 1 + (50).-5
a 51 = a 1 + (-250)
a 51 = a 1 - 250
a 1 - 250 = a 51
a 1 - 250 = 243
a 1 = 243 + 250
a 1 = 493
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás